Urban Sustainability Indicator Systems for the Canton of La Libertad (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The objective of the research is to design a model of urban sustainabilityindicators to strengthen the local development of the canton of LaLibertad; urban sustainability indicators have been seen as signals thatmark the progress of the achievement of the objectives and goals set inthe urban planning process, and allow making relevant and timelydecisions. The types of research used are descriptive and analytical, bymeasuring variables through the deductive and inductive methods; apopulation of 48671 was considered, corresponding to the number ofinhabitants of the canton of La Libertad between the ages of 20 and64, from which a sample of 356 people was selected. The proposedmodel MSUCLL - 2021, is a model determined in relation to the criteriadetermined in the research, thus allowing the improvement of criticalfactors that affect urban sustainability; it includes 4 axes: compactnessand functionality, urban complexity, efficiency, and social cohesion.